CORRUPTION AND POST-CONFLICT PEACEBUILDING: SELLING THE PEACE? - Cheng, CS; Zaum, D (Scientia Militaria - South African Journal of Military Studies, 2015)
Corruption and post-conflict peacebuilding: Selling the peace? is a veritable gold mine. Its organisation is intelligent and coherent, and its range and coverage are appropriately encyclopaedic. This volume deals with the theoretical issues around the concepts of corruption and post-conflict peacebuilding. It analyses the effect of corruption in post-conflict times and peacebuilding on the basis of a particular conceptual framework. Although this conceptual framework serves as the basis of this book, it presents many other theories and empirical evidence to illuminate these complex topics and also draws from every relevant discipline related to the issue of corruption and post-conflict peacebuilding. In this regard, the volume provides numerous examples by citing cases from different countries.